Experimental evaluation of Mode II fracture and microstructure of matrix-aggregate bond of concrete with crushed limestone - Grzegorz Ludwik Golewski; Xinyue Xi; Yuanxun Zheng; Jingbo Zhuo; Peng Zhang; Rafał Panek (Case Studies in Construction Materials)
Due to the shortage of construction aggregates carbonate rock aggregates – including mainly limestone aggregates – have long been used in structural concrete in many countries worldwide. On the other hand, earlier tests on the shear fracture toughness of concretes with limestone aggregates was very limited and even abandoned for many years. From above reasons in this paper completely new fracture toughness tests performed according to the Mode II fracture for limestone concretes with different grain size distribution. Two types of aggregate grain were used, with maximum grain sizes of 8 mm (LM-1 series concrete) and 16 mm (LM-2 series concrete). During the experiments the critical stress-intensity factor (KIIc) and critical unit work of failure (JIIc) were determined. Moreover, the size width of microcracks (Wc) in the ITZ area were examined. Based on the conducted studies it was found that higher values of fracture mechanics parameters were noted as the grain sizes of the aggregate used increased. The increases of fracture mechanics parameters were noticeably greater in the LM-2 concrete compared to the results for the LM-1 concrete, specifically by 27 % for KIIc and 35 % for JIIc. On the other hand increasing the aggregate size from 2 to 8 mm to 8–16 mm led to a 33 % reduction in Wc of limestone concretes. The novelty of the research undertaken resulting from the fact that exploring the properties of concretes with limestone aggregates using Mode II fracture is an important aspect of evaluating the durability and safety of concrete structures subjected mainly to shear forces.